The Structural Model for Predicting Marital Burnout Based on Attachment Styles with the Mediating Role of Marital Self-Regulation and Marital Intimacy in Married Individuals - Hasani Pouya, Farank; Sobhi Gharamaleki, Naser; Mirzahosseini, Hassan (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to predict marital burnout in individuals married for 5 to 10 years based on attachment styles, with the mediating roles of marital self-regulation and marital intimacy.Methods and Materials: This study was analytical-correlational in nature, employing path analysis. The sample consisted of 384 married individuals (164 men and 220 women) who were selected through convenience sampling. The participants were aged between 25 and 45, with a marriage duration of 5 to 10 years. Data were collected using validated questionnaires, including the Marital Burnout Scale (Kayser, 1996), the Revised Adult Attachment Scale (Collins & Read, 1990), the Behavioral Self-Regulation for Effective Relationships Scale (Wilson et al., 2005), and the Intimacy Scale (Walker & Thompson, 1983). SPSS and Amos software were used for data analysis, applying structural equation modeling (SEM) to examine direct and indirect effects.Findings: The results indicated that marital self-regulation and intimacy mediated the relationship between attachment styles and marital burnout. Avoidant and anxious attachment styles positively predicted marital burnout, while secure attachment negatively predicted it. Additionally, self-regulation and intimacy were significant mediators, with higher levels of self-regulation and intimacy associated with lower marital burnout. Avoidant and anxious attachment styles negatively influenced self-regulation and intimacy, which in turn increased marital burnout.Conclusion: The study concluded that attachment styles significantly impact marital burnout, with self-regulation and intimacy playing crucial mediating roles. Individuals with insecure attachment styles (avoidant and anxious) are more prone to marital burnout, whereas secure attachment leads to lower burnout. Interventions aimed at improving self-regulation and intimacy in couples may help mitigate the effects of insecure attachment styles on marital burnout.